Acute cerebral microbleeds in refractory status epilepticus. Issue 5 (8th February 2013) - Jeon, Sang‐Beom; Parikh, Gunjan; Alex Choi, H.; Lee, Kiwon; Lee, Jong Hwan; Schmidt, J. Michael; Badjatia, Neeraj; Mayer, Stephan A.; Claassen, Jan
Summary Cerebral microbleeds (CMBs) are commonly found in patients with stroke and cerebral amyloid angiopathy. However, there have been no reports of CMBs or their acute appearance in patients with status epilepticus. Herein we describe two patients with refractory status epilepticus of uncertain origin. Both patients were previously healthy, and their initial imaging showed no underlying CMBs. One patient's follow‐up susceptibility‐weighted imaging 29 days after initial imaging showed 63 new CMBs. The other patient's follow‐up susceptibility‐weighted imaging 41 days after initial imaging showed 14 new CMBs. Multimodal neuromonitoring revealed increase in lactate–pyruvate ratio, decrease in partial brain tissue oxygen tension, increase in pressure reactivity index, and fluctuations of blood pressure and cerebral perfusion pressure. This report demonstrates that multiple new CMBs may develop in patients with refractory status epilepticus (SE).